Effect of Body Condition Score on Reproductive Performance and Chest Girth of Bali cows in Different Rearing Systems - Dinda Ayu Permata Sari; S Said; Nahrowi Nahrowi; R Priyanto; Muladno Muladno (Jurnal Ilmu Ternak dan Veteriner, 2021)
Nutrition and rearing systems are some of the main factors affecting productivity of cows. Body condition score (BCS) is a method used to assess nutritional status and evaluate rearing systems of each animal. This study was done to analyze effect of BCS on reproductive performance and chest girth of Bali cow in different rearing systems. This study was conducted at the Field Station of Sekolah Peternakan Rakyat Kuamang Abadi, Bungo Regency, Jambi, Indonesia. A total of 62 heads of Bali cow with BCS of 2, 3, and 4 (scale 1-5) reared on intensive, semi-intensive and extensive systems were used in this study. This study was conducted using survey and direct observation. Variables observed were as follows: BCS, calving interval (CI), days open (DO), service per conception (S/C) and chest girth (CG). Data were analyzed using simple correlation and regression analysis in SPPS, followed by descriptive analysis. Result showed that the BCS of Bali cow in different rearing systems did not affect CI, DO, S/C and CG. BCS had a weak correlation coefficient (r), with the reproductive performance of CI, DO, and S/C at 0.09, 0.09, and 0.08, respectively. In addition, the relationship between BCS and CG was highly significant, with a correlation coefficient (r) of 0.532. Therefore, BCS had a positive relationship with CI, DO, S/C, and CG. Moreover, BCS cannot be used as the only indicator to assess the reproductive performance of Bali cow in different rearing systems.